The Influence of the Plant Biomass Pyrolysis Conditions on the Structure of Biochars and Sorption Properties - Bernadetta Kaźmierczak; Jolanta Drabik; Paweł Radulski; Anna Kaczmarczyk; Edyta Osuch-Słomka (Molecules)
The aim of this work was to obtain biochar materials from plant biomass and to determine the changes occurring under the conditions of the pyrolysis process and physical activation, as well as to characterize the physicochemical characteristics of the produced products in terms of their practical use. The pyrolysis process was carried out at a temperature of 700 °C, under the flow of a protective gas, i.e., carbon dioxide, at a rate of 5.0 L/min. The pyrolysis processes were carried out in the absence and presence of an activating agent. For ecological safety, physical activation using water vapor was chosen. In the next stage of the work, biochars were produced and subjected to detailed physicochemical analysis. A scanning electron microscope with energy-dispersive SEM/EDS was used to determine the microstructure and changes in the chemical composition of the biochars. FTIR spectrophotometry was used to identify the functional groups present in the structures of biochars and to indicate changes occurring in the biomass during pyrolysis. Meanwhile, Raman spectroscopy was used to assess the ordering of the biochar structures based on the identification of spectral signals. The description of the specific surface areas of the biochars was made possible by studies conducted using a physical and chemical adsorption analyzer. Based on the obtained research results, the elementary structure, surface development, presence of functional groups on the surfaces of biochars and changes in the structure before and after activation with water vapor were determined. It was found that the biochars had functional groups, a well-developed specific surface area that increased after activation with water vapor, micropores and mesopores, as well as changes in structure under the influence of physical activation. It has been shown that the presence of functional groups influences the hydrogen sulfide sorption capacity.